PENGAWASAN OLEH DINAS PERHUBUNGAN PROVINSI RIAU TERHADAP OPERASIONALISASI PELABUHAN PENYEBRANGAN RO-RO DI KOTA DUMAI TAHUN 2012-2013 - Meli Oktalisah; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Problems that occur on Ro-Ro ferry ports of Dumai ie lack warships in the harbor, so that every day many crossings that can not take across in because the capacity of passengers or goods that have been filled. Supposedly with the applicable provisions fleet on Ro-Ro port of Dumai it consists of 3 (three) fleet, but now only amounts to 1 (one) fleet. It is certainly not in accordance with existing regulations. With so activity on Ro-Ro ferry ports Dumai ineffective and the practice of extortion committed by unscrupulous Riau Provincial Transport Department staff to passenger ferry ports. The purpose of this study is to find out to find out the supervision of the Riau Provincial Transport Department Operations City Harbour Crossing in Dumai and to determine the factors that influence the control of the Riau Provincial Transport DepartmentinDumai.Methods This study uses qualitative research methods research types. This research was conducted in the city of Dumai in this area where there are several ferry ports which many passengers crowded. But there are still many shortcomings that exist in some of its ports as less fleet and lack of safety for passenger ships. While the data collection by using the technique of interviewing informants who are competent in their field as well as by direct observation of the authors in the field. The results of this study conclude In monitoring indicators funds / costs, weak oversight made Riau Provincial Transport Department for the operation of ferry ports, especially on the operational budget problems in department transport. Crossing the harbor must pay for their own purposes any crossing port operations so that they do not know the practice of extortion (extortion) against unscrupulous Riau Provincial Transport Department. So here authorized agency Riau Provincial Transport Department should work hard to improve oversight of the operation of ferry ports and monitoring should be performed continuously so that no more Riau Provincial Transport Department officers who conduct illegal charges against the passenger Ro-Ro ferry ports of Dumai.Keywords: Monitoring, Ro-Ro Ferry Port.